Gender construction in career and household role distribution among married millennial couples - Prihatini, Sylvia Yunita; Pudji Astuti, Tri Marhaeni; Handoyo, Eko (JESS (Journal of Educational Social Studies), 2021)
This study aims to analyze the impact of gender construction in married millennial couples, particularly in career and household role distribution. It was a qualitative study using phenomenology format. The data collection was done by applying observation and in-depth interview. The data analyses used construction theory and qualitative analysis. Based on the multiple analyses, women living in the Graha Surya and Vila Dawung act both as office workers and housewives. Besides supporting the family economy, they are allowed to work to avoid getting bored at home, gain experience outside, and make friends. Gender bias in the household life of millennial couples seems blurred as wives are also required to help meet family needs. Married couples who synergistically work also provide flexibility in the financial management of their respective salaries. This way, family decisions depend not only on the husband; discussions on various issues due to equal position. Constraints faced by career married couples are the limited time to gather with family and take care of the household.